2021
DOI: 10.3389/fnins.2021.624653
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Mirror System in Influencing Musicians’ Evaluation of Musical Creativity: A tDCS Study

Abstract: Evidence reported in the literature suggests that the mirror system not only plays a role in recognizing motor action but also fosters a better understanding of other people because it helps an individual assume another’s perspective. This led to the idea, supported by research findings, that people with higher empathy scores should show higher activation of the mirror system. Recently, it has been hypothesized that a purely auditory mirror system exists. In this study, we aimed to explore the possibility that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Система зеркальных нейронов (СЗН) привлекает к себе внимание исследователей с момента её первого обнаружения у макак [1]. Дальнейшее изучение СЗН у человека позволило выявить наличие слуховой зеркальной системы, задействованной в процессе эмпатического сопереживания [2] и музыкального творчества [3]. СЗН облегчает имитацию действий после наблюдения за ними, таким образом способствуя обучению новым навыкам и улучшению понимания наблюдаемой активности.…”
Section: аннотацияunclassified
See 1 more Smart Citation
“…Система зеркальных нейронов (СЗН) привлекает к себе внимание исследователей с момента её первого обнаружения у макак [1]. Дальнейшее изучение СЗН у человека позволило выявить наличие слуховой зеркальной системы, задействованной в процессе эмпатического сопереживания [2] и музыкального творчества [3]. СЗН облегчает имитацию действий после наблюдения за ними, таким образом способствуя обучению новым навыкам и улучшению понимания наблюдаемой активности.…”
Section: аннотацияunclassified
“…
The mirror neuron system (MNS) has been a captivating area of research since its discovery in macaque monkeys [1]. Researchers have established the role and presence of the human auditory mirror system in both empathy [2] and musical creativity [3]. As well, the mirror system allows to learn new behaviors by observation, facilitating knowledge acquisition and action understanding.
…”
mentioning
confidence: 99%
“…The mirror neuron system plays an important role in imitation activities, interpersonal learning, and other behaviors (Oberman et al, 2007;Mainieri et al, 2013;Meng Yuan et al, 2018), and autism is considered in part to be related to dysfunction in the mirror neuron system (Hamilton, 2008). A previous study has shown that cathode tDCS significantly reduced musicians' assessment of musical creativity, which was related to the mediating effect of empathy (Colombo et al, 2021). Anodal tDCS intervention on the right inferior frontal gyrus of healthy subjects is thought to induce imitative behavior in social interaction (Hogeveen et al, 2015).…”
Section: The Improvement Of Teamwork By Transcranial Electrical Stimu...mentioning
confidence: 99%